Flow patterns of basic operating modes of oscillating heat pipes - Алексеїк, Євгеній Сергійович; Кравець, Володимир Юрійович (Eastern-European Journal of Enterprise Technologies, 2012)
The results of visualization of closed loop pulsating heat pipes with 1, 4, 6 8, 10 turns at different orientation in space are presented. Flow patterns of basic operating modes are described